Cardiopulmonary, biomarkers, and vascular responses to acute hypoxia following cardiac transplantation. Issue 9 (18th August 2018) - Sanz‐de la Garza, Maria; Iannino, Nadia; Finnerty, Vincent; Mansour, Asmaa; Blondeau, Lucie; Gayda, Mathieu; Chaar, Diana; Sirois, Martin G.; Racine, Normand; de Denus, Simon; Harel, François; White, Michel
Abstract: Previous studies have suggested good adaptation of cardiac transplant (CTx) recipients to exposure to a high altitude. No studies have investigated the cardiopulmonary and biomarker responses to acute hypoxic challenges following CTx. Thirty‐six CTx recipients and 17 age‐matched healthy controls (HC) were recruited. Sixteen (16) patients (42%) had cardiac allograft vasculopathy (CAV). Cardiopulmonary responses to maximal and submaximal exercise at 21% O2, 20‐minutes hypoxia (11.5% O2 ), and following a 10‐minute exposure to 11.5% O2 using 30% of peak power output were completed. Vascular endothelial growth factor (VEGF), interleukin‐6 (IL‐6), suppression of tumorigenicity 2 (ST2) were measured at baseline and at peak stress. Endothelial peripheral function was assessed using near‐infrared spectroscopy. Compared with HC, CTx presented a lesser O2 desaturation both at rest (−19.4 ± 6.8 [CTx] vs −24.2 ± 6.0% O2 [HC], P < 0.05) and following exercise (−23.2 ± 4.9 [CTx] vs −26.2 ± 4.7% O2 [HC], P < 0.05). CTx patients exhibited a significant decrease in peak oxygen uptake. IL‐6 and VEGF levels were significantly higher in CTx recipients in basal conditions but did not change in response to acute stress. CTx patients exhibit a favorable ventilatory and overall response to hypoxic stress. These data provide further insights on the good adaptability of CTx to exposure to high altitude.